Short Communication: Curcuma wanenlueanga (Zingiberaceae), a new species of subgenus Curcuma from Thailand - Surapon Saensouk; Thawatphong Boonma; ADISAK THOMUDTHA; PARIYA THOMUDTHA; Piyaporn Saensouk (Society for Indonesian Biodiversity, 2021)
Abstract. Saensouk S, Boonma T, Thomudtha A, Thomudtha P, Saensouk P. 2021. Short Communication: Curcuma wanenlueanga (Zingiberaceae), a new species of subgenus Curcuma from Thailand. Biodiversitas 22: 2988-2994. Curcuma wanenlueanga Saensouk, Thomudtha & Boonma, a new species of Curcuma subgenus Curcuma (Zingiberaceae) from Thailand was described with detailed illustrations, and photographs. The dominant morphological description is terminal inflorescence, leaf adaxially green with reddish-purple along the midrib, leaf-sheath with reddish-brown tinge. Moreover, the color and smell rhizome of C. wanenlueanga has yellow with a darker core internally. It is distributed in Mae Hong Son Province, Northern Thailand, and cultivated throughout the country, i.e. Nakhon Nayok, Maha Sarakham, Chiang Mai, Tak, Chantaburi, Suratthani, and Kanchanaburi Provinces. It is used as Thai traditional medicinal. It grows in in sandy loam soil and well-drained in the mixed-deciduous forest, at elevation 700-900 m asl. It is accompanied by a revised key to 26 species of Curcuma subgenus Curcuma from Thailand.